Price Discrimination and Retail Configuration - Shepard, Andrea (Journal of Political Economy, 1991)
The hypothesis that price discrimination based on willingness-to-pay for quality can occur in multifirm markets is confirmed using microdata on gasoline retailing. A test that discriminates between price structures associated with discrimination and with cost-driven, competitive differentials is developed and implemented with controls for variation in outlet and market characteristics. A second test based on profitability variation rejects a competitive, peak-load pricing explanation for the observed price dispersion. The data suggest that price discrimination at the retail level adds at least nine cents a gallon to the average price of full-service gasoline. Copyright 1991 by University of Chicago Press.